A new natural product compound benjaminin from Calophyllum benjaminum - Muhamad Sahimi, Muhamad Syarik; Ee, Gwendoline Cheng Lian; Mahaiyiddin, A. G.; Daud, Shaari; Teh, Soek Sin; See, Irene; Sukari, Mohd Aspollah (Universiti Putra Malaysia Press, 2015)
Our detailed study on the chemical constituents of the stem bark of Calophyllum benjaminum and Calophyllum javanicum has resulted in one new coumarin benjaminin (1), five xanthones fuscaxanthone C (2), β-mangostin (3), thwaitesixanthone (4), dombakinaxanthone (5) and caloxanthone A (6), together with four common triterpenes friedelin (7), β-sitosterol (8), lupeol (9) and stigmasterol (10). The structures of these compounds were elucidated using NMR, FTIR and GCMS.